Access to Justice for Disadvantaged Communities - Mayo, Marjorie (2014)
Access to justice for all, regardless of the ability to pay, has been a core democratic value. But this basic human right has come under threat through wider processes of restructuring, with an increasingly market-led approach to the provision of welfare. Professionals and volunteers in Law Centres in Britain are struggling to provide legal advice and access to welfare rights to disadvantaged communities. Drawing upon original research, this unique study explores how strategies to safeguard these vital services might be developed in ways that strengthen rather than undermine the basic ethics and principles of public service provision. The book explores how such strategies might strengthen the position of those who provide, as well as those who need, public services, and ways to empower communities to work more effectively with professionals and progressive organisations in the pursuit of rights and social justice agendas more widely.